Aplikasi Watermarking Dengan Algoritma Aes Untuk Pemberian Data Hak Cipta Pada File Audio - Durachman, Yusuf (Prosiding SNATIKA Vol 01 (2011), 2011)
Watermarking audio files has recently become the attention focus. This is primarily due to faster data transmission rates on the Internet, which has allowed the often illegal proliferation of digital audio files. Watermarking may give the ability to enforce copyright protection of digital audio files products. The difficulties in watermarking audio lie in both the desire to preserve file quality and the need for the watermark to remain intact after a number of possibly damaging file operations. This topic discusses about watermarking on audio file with AES (Advanced Encryption Standard) â Rinjdael algorithms with embedding procedure and extraction to purpose protection Watermarking method to used embedding process and extraction is low bit coding method. None of the transformations to and from frequency domain are performed either in embedding or extraction part of the proposed scheme. Testing process done using 5 ways such as suitability of process and data, audio quality, audio size and the last is data robustness, those result showed that embedded watermark introduces uncertainly and the embedded watermark into audio signal very is difficult to be detected by human auditory system. Keywords : Watermarking, AES (Advanced Encryption Standard), low bit coding, audio file, copyright